Association and haplotype analysis of TCF7L2 gene variants with development of obesity in type 2 diabetic patients among Northern Iranians - Abbaspour, Saima; Keshavarz, Parvaneh; Sharafshah, Alireza (Journal of diabetes and metabolic disorders, 2025)
Introduction The current study aimed to investigate the possible association of TCF7L2 well-acknowledged SNPs including rs7903146, rs11196205, and rs12255372 with obesity occurrence among northern Iranians with Type 2 Diabetes Mellitus (T2DM). Materials and methods DNA extraction from whole blood of all subjects was done by salting-out technique. A total of 483 T2DM patients (307 T2DM individuals without Obesity and 176 T2DM individuals with Obesity) were genotyped through TaqMan assay technology. Statistical analyses were computed by ASSOTEST, Haploview (ver. 4.2), SPSS (ver. 27), and Python (ver. 3.13). Results Clinical characteristics assessments between the study groups showed that there was significant association for the gender type of T2DM individuals for being obese ( P < 0.001, males were at higher risk). Importantly, the genetic association analysis uncovered that rs7903146 was associated with the susceptibility of Obesity among T2DM people ( P = 0.021, OR = 0.60[0.38–0.93]) in a recessive model of inheritance. Genotype-Phenotype association analysis indicated no significant associations. Finally, using Python programming and based on libraries including Pandas, NumPy, SciPy, and statsmodels, 6 haplotypes with frequency higher than 0.05 found. One significant haplotype including TT-GG-GT ( P = 0.03) found, however, following p-value adjustment, it was not significant. Conclusion In conclusion, this study indicated various significant results highlighting on the association of rs7903146 with susceptibility to obesity among northern Iranians with T2DM. Importantly, this study showed that females are more at risk of getting obesity than males.